Comparative Study of Inhaler Device Handling Technique and Risk Factors for Critical Inhaler Errors in Korean COPD Patients - Jang, Jong Geol (Int J Chron Obstruct Pulmon Dis, 2021)
OBJECTIVE: Critical inhaler handling errors are associated with an increased risk of adverse outcomes in patients with chronic obstructive pulmonary disease (COPD). However, real-world data on inhaler device handling techniques and the risk factors for critical inhaler errors in the Asian population have been examined in only a few studies. We evaluated the rates and risk factors for critical inhaler errors in the COPD population in Korea. METHODS: COPD patients were prospectively enrolled from January 2018 to November 2019. An advanced practice nurse evaluated their inhaler technique. The 308 inhalers used by the 261 participants in this study included dry powder inhalers (DPIs; Turbuhaler, Breezhaler, Ellipta, Diskus, Genuair), a soft mist inhaler (SMI; Respimat), and pressurized metered dose inhalers (pMDIs). RESULTS: The percentage critical errors for Turbuhaler, Breezhaler, Ellipta, Diskus, Genuair, Respimat, and pMDI usage were 60.0%, 41.0%, 27.8%, 12.5%, 44.4%, 45.5%, and 55.0%, respectively. In the multivariate analyses, female sex, short COPD duration, dissatisfaction with the inhaler (assessed by FSI-10), and moderate acute exacerbations (AEs) in the prior year were independent risk factors for any critical error in the DPI group. In the SMI group, a low education level and frequent AEs in the prior year were independent risk factors for any critical error, whereas a high COPD assessment test (CAT) score was the only risk factor in the pMDI group. CONCLUSION: Critical inhaler errors are common among patients with COPD, regardless of their preferred inhaler device. The rates and risk factors for critical inhaler errors differed among patients using different devices. Optimal device selection considering the risk factors of inhaler misusage will improve disease control in COPD patients.